2021
DOI: 10.1371/journal.pone.0256811
|View full text |Cite
|
Sign up to set email alerts
|

Gender with marital status, cultural differences, and vulnerability to hypertension: Findings from the national survey for noncommunicable disease risk factors and mental health using WHO STEPS in Bhutan

Abstract: Cardiovascular disease is the leading cause of death in the Kingdom of Bhutan. Thus, the early detection and prevention of hypertension is critical for reducing cardiovascular disease. However, the influence of sociocultural factors on vulnerability to hypertension needs further investigation. This study performed secondary data analysis on 1,909 individuals in a cross-sectional study (the National survey for noncommunicable disease risk factors and mental health using World Health Organization (WHO) STEPS app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Furthermore, the associations of education and marital status with NCDs were similar to past studies showing that lower levels of education and being divorced, separated or widowed increased the odds of having NCDs in comparison to uneducated and never married women [ 52 , 53 ]. Factors such as hormonal changes in reproductive cycle, chronic stress, women’s sociocultural vulnerability and marital relationship satisfaction might have influenced the observed association of marital status with NCD prevalence [ 54 , 55 ]. Future research is necessary to confirm this association and explore the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the associations of education and marital status with NCDs were similar to past studies showing that lower levels of education and being divorced, separated or widowed increased the odds of having NCDs in comparison to uneducated and never married women [ 52 , 53 ]. Factors such as hormonal changes in reproductive cycle, chronic stress, women’s sociocultural vulnerability and marital relationship satisfaction might have influenced the observed association of marital status with NCD prevalence [ 54 , 55 ]. Future research is necessary to confirm this association and explore the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Single male have a higher risk of hypertension than married male, and unmarried female have a lower risk of hypertension than married female; thus, health status differs according to marital status and sex [ 6 ]. The prevalence of hypertension was higher in married female or female who were separated, divorced or widowed than in female living together with their spouses, and the prevalence of hypertension differed according to marital status and sex [ 8 ]. Economic difficulties and low SES, as well as divorce or a deceased spouse, were important risk factors for hypertension in female [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the effect of male marital status on hypertension, unmarried male had a high risk of hypertension [ 6 , 9 ]. A study on the effect of female’s marital status on hypertension found that separation, divorce, and a deceased spouse affected hypertension in female [ 8 ]. In some studies, divorced female had a higher risk of hypertension [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations